Flexural and Compression Superiority of Sewage Sledge Ash Concrete - David, Thevaneyan Krishta; Krishnamoorthy, Renga Rao (International Journal of Sustainable Construction Engineering and Technology, 2022)
The sustainability of environment has become a global issue, and several researches have been conducted in order to uncover possible and trustworthy solutions for lowering the problem and increasing one’s quality of life. Wastewater treatment produces sludge, which is an unavoidable byproduct. Landfilling, ocean dumping, and spreading over reclaimed territory are all common ways of disposal. However, these popular sludge disposal methods represent a significant dilemma since they can pollute the environment, including the air, land, and water. Since sewage sludge can be treated to produce sewage sludge ash (SSA), which has the potential to replace certain percentages of cement, studies on sewage sludge have been popular in recent years. Many studies have been done to use the SSA in lightweight concrete, bricks, and aerated concrete because nations like Spain and the United Kingdom have problems disposing of sewage sludge. This study focuses on the flexural and compression strength of the sewage sludge ash (SSA) concrete for 3, 7 and 21 days of curing relatively to its density. In this study 10 percentages of SSA was used as a replacement to cement and fine aggregates. The flexural strength of concrete for cement replaced with SSA was lower than the control sample but it has an higher early flexural strength. The flexural strength of concrete for fine aggregate replaced with SSA was higher compared to the control sample. Comparatively, the compressive strength of concrete when SSA used as combination of cement and fine aggregate replacement also give higher value compare to control sample.